Soret and chemical reaction effects on unsteady two-dimensional natural convection along a vertical plate - Raju, S.S.K. (American Institute of Physics Inc., 2014)
In this paper, a numerical solution of the unsteady two-dimensional natural convection along a vertical plate in the presence of Soret and chemical reaction effects is presented. The governing non-dimensional coupled non-linear partial differential equations have been evaluated by using an implicit finite-difference technique of Crank-Nicolson scheme. Numerical predictions for the velocity, concentration, local and average skin-friction and Sherwood number for distinct values of chemical reaction parameter and Soret number are plotted graphically. It is found that the fluid velocity and concentration decreases while increasing chemical reaction parameter whereas an increase in the Soret number increases the fluid velocity and concentration. Â© 2014 AIP Publishing LLC.